Penerapan Algoritma FP-Growth Untuk Mengetahui Pola Pada Data Transaksi Percetakan (Studi Kasus Java Printing Batujajar) - Sugianto, Castaka Agus; Sukmawati, Dini (Journal of Information Technology, 2023)
Transaction data in the printing industry provides valuable insights into concurrently favored products by customers within a specific timeframe. Java Printing Batujajar has recorded printing transactions over the past 2 years. However, the lack of data management has led to disorganized raw material inventory, resulting in many unprocessed transaction records. The collected data consists of 704 printing transaction records from 2021 to 2022. Consequently, a solution is needed to identify patterns within this transaction data. This research aims to employ the association method with FP-Growth algorithm using the RapidMiner software. The research findings reveal an association between two products: "Buku Yasin L 208hl" (Complete/using elbow and tassel ribbon, 208 pages) and "Buku Yasin L 224hl" (Complete/using elbow and tassel ribbon, 224 pages). Both products exhibit the highest support value, accounting for 11.5% of total transactions, indicating their frequent simultaneous purchases. Moreover, the confidence value for the association between these two products reaches 100%, implying that if a customer purchases "Buku Yasin L 208hl," they will certainly buy "Buku Yasin L 224hl" as well. The test results indicate that by adjusting experimental parameters, higher support and confidence values are achieved compared to using default parameters. This signifies that experimental testing is more effective in discovering product associations and providing valuable information for optimizing the arrangement and storage of related raw materials.